2014
DOI: 10.3892/or.2014.3637
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the miR-212/132 cluster suppresses proliferation of human lung cancer cells

Abstract: Abstract. Lung cancer is the leading cause of cancer-related mortality worldwide. microRNAs (miRNAs) are small posttranscriptional regulatory non-coding RNAs that function as oncogenes or tumor suppressors in human cancers. Emerging evidence reveals that deregulation of miRNAs contributes to the progression of human lung cancer, which is the leading cause of cancer-related deaths worldwide. In the present study, we found that upregulation of the miR-212/132 cluster significantly suppressed the growth and focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…Further the significant upregulation of CDK1A in osmotically stressed CHO cells together with G1‐phase arrest, increased q ATP and enhanced q p may elucidate CDK1A's q p enhancing role that had been described in previous cell cycle engineering studies . Overexpression of miR‐132, miR‐194 and miR‐215 may potentially enhance q p as this was shown to induce p53/CDK1A(p21) mediated cell cycle arrest in G1‐phase . The hypothesized regulatory connection between miR‐183, EGR 1 and cell cycle arrest together with the q p enhancing effect described by Strotbek et al (2013) give point to miR‐183 as the most promising candidate for subsequent cell line engineering studies .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Further the significant upregulation of CDK1A in osmotically stressed CHO cells together with G1‐phase arrest, increased q ATP and enhanced q p may elucidate CDK1A's q p enhancing role that had been described in previous cell cycle engineering studies . Overexpression of miR‐132, miR‐194 and miR‐215 may potentially enhance q p as this was shown to induce p53/CDK1A(p21) mediated cell cycle arrest in G1‐phase . The hypothesized regulatory connection between miR‐183, EGR 1 and cell cycle arrest together with the q p enhancing effect described by Strotbek et al (2013) give point to miR‐183 as the most promising candidate for subsequent cell line engineering studies .…”
Section: Discussionmentioning
confidence: 74%
“…An either oncogenic or tumor suppressive role in cancer cells was reported for miR‐132, miR‐183 and miR‐182 . Overexpression of miR‐132, miR‐194 and miR‐215 resulted in a p53/CDK1A mediated cell cycle arrest in G1‐phase . Increased product titers and enhanced q p in combination with a decrease in cell growth was reported for recombinant CHO cell lines which had transiently been transfected with human miR‐183 .…”
Section: Discussionmentioning
confidence: 96%
“…The expression of miRNA-320 in C33AR cells was significantly lower than that in C33A cells. Several differentially expressed miRNAs in this profile were previously reported to have a role in tumorigenesis, including the development of radioresistance (17,18). These results indicated that differentially expressed miRNAs may contribute to the acquisition of radioresistance in cervical cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been demonstrated that miR-212/132 is deregulated in cancers of various forms, including B cell leukemias, and that up-regulation of miR-212/132 in lung cancers inhibits proliferation and progression of the disease (Pede et al, 2013;Zhang et al, 2014;Jiang et al, 2015;Tavolaro et al, 2015). We found that enforced expression of miR-132 in donor cells from E-myc mice, which are prone to develop pre-B and immature B cell lymphomas and leukemias, had a strong protective effect on cancer development.…”
Section: Microrna-132 Protects E-myc Mice From B Cell Leukemia Develmentioning
confidence: 99%